Comparison of CAPM Results With The Beta Reward Approach In The Trade, Services, and Investment Sector At The Kompas100 Index In Indonesia - Handri Handri (IAIN Palopo, 2023)
This study aims to compare the estimated yield between the CAPM model and the Beta Reward approach in calculating. Beta shares in Trade companies, Services, and Investments that are incorporated in the Kompas100 index in Indonesia. The Data used is the closing price of the company's shares during the study period from January 2010 to December 2019. In this study, there are 4 four companies that are consistent. The results showed that the Beta Reward method has R-squared, RMSE, and MAE is better at predicting company stock returns compared to the CAPM method. These findings indicate a systematic relationship between Beta reward with stock return in Indonesia.